RESISTANCE AND ENZYME ASSESMENT OF THE PINK BOLLWORM, PECTINOPHORA GOSSYPIELLA (SAUNDERS) TO SPINOSAD - K. H. Sabry; Nahed F. Abdel-Aziz (Journal of Animal and Plant Sciences, 2013)
Resistance of the pink bollworm, Pectinophora gossypiella (Saunders) to spinosad was examined under laboratory conditions during 20 successive generations. After 20 generations of selection pressure by spinosad the resistance ratio was increased to 54.1 –fold. The resistance ratios fluctuated during the selection period. The highest resistance ratio was occurred in F16, it was 62.5 –fold. No cross resistance was observed between spinosad resistant colony and buprofezin, pyriproxyfen, lambda-cyhalothrin, thiamethoxam, chlorpyrifos and carbaryl. The resistance ratio decreased when piperonyl butoxide was mixed with spinosad. The activities of acetylcholine esterase and total protein were increased in spinosad resistant colony compared with the susceptible colony. These results confirmed that enzyme detoxification mechanism is considered one of the main mechanism of resistance to spinosad and the use of pesticides rotation play an important role in pesticide resistance management. These findings also, indicate that the ability of this new biopesticide (spinosad) to build up of resistance in the pink bollworm after the second generation of selection pressure. So, these results suggested that this biopesticide can be used twice only during the same season without any pest resistance.
Keywords: Pectinophora gossypiella; spinosad; enzyme detoxification; cross resistance; resistance ratio